A differential role for actin during the life cycle of Trypanosoma brucei - García-Salcedo, José A (Nature Publishing Group, 2004)
Actin is expressed at similar levels but in different locations in bloodstream and procyclic forms of Trypanosoma brucei. In bloodstream forms actin colocalizes with the highly polarized endocytic pathway, whereas in procyclic forms it is distributed throughout the cell. RNA interference demonstrated that in bloodstream forms, actin is an essential protein. Depletion of actin resulted in a rapid arrest of cell division, termination of vesicular traffic from the flagellar pocket membrane leading to gross enlargement of the pocket, loss of endocytic activity and eventually cell death. These results indicate that actin is required for the formation of coated vesicles from the flagellar pocket membrane, which is the first step in the endocytic pathway. Although loss of actin in procyclic cells did not affect growth, the trans region of the Golgi became distorted and enlarged and appeared to give rise to a heterogeneous population of vesicles. However, the flagellar pocket was not affected. These findings suggest that trypanosomes have different functional requirements for actin during the bloodstream and procyclic phases of the life cycle.